Digital Teaching Materials for Fantasy Stories Oriented Towards Developing Critical Thinking Skills in SMP/MTS Students - Nugroho, Beni; Kusmana, Suherli; Wilsa, Jaja (International Journal of Educational Research Excellence (IJERE), 2025)
This research aims to find out and meet the needs of teaching materials, especially fantasy story text materials in digital form and their implementation, so that they can foster critical thinking skills in junior high school/MT students. The method used in this research was research and development, and the model used was the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). The results obtained are digital teaching materials for fantasy story texts oriented towards cultivating critical thinking skills suitable for use as teaching materials for junior high school/MT students. Learning resources in the form of several fantasy story texts from various books and other sources that were analyzed met the requirements structurally, linguistically, and in critical thinking aspects as teaching materials developed in the form of digital teaching materials. The development of digital teaching materials for fantasy story texts is adjusted to indicators of competency achievement and learning outcomes validated by experts to obtain a category of teaching materials suitable for use in SMP/MTs in Indramayu Regency. Based on the results of testing teaching materials in learning, it is known that these teaching materials are effective in cultivating critical thinking skills among junior high school/MT students